2005
DOI: 10.1002/pat.577
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric PS‐block‐(PS‐co‐PB)‐block‐PS block copolymers: morphology and deformation behavior of star block copolymer/PS blends

Abstract: The morphology and deformation behavior of blends comprising an asymmetric styrene/butadiene star block copolymer and polystyrene homopolymer (hPS) were investigated by means of transmission electron microscopy (TEM) and uniaxial tensile testing. The hPS samples used had a wide range of molecular weights. In spite of the high polystyrene (PS) content, the star block copolymer exhibited a morphology consisting apparently of a rubbery matrix, attributable to its asymmetric architecture and presence of polystyren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, surprisingly, under the given processing conditions, and with the special parent block copolymer architecture, the nanostructures of the block copolymer is maintained; there is no sign of macrophase‐separation as one would expect in the block copolymer blends comprising polystyrene with much higher molecular weight than the size of the corresponding block of the block copolymer. It should be noted that the molecular weight of GPPS used to prepare the blends has higher molecular weight (190,000 g/mol) . The PS chains should act as chains adhered feebly to the polystyrene domains of the block copolymer in the so called dry‐brush regime.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…However, surprisingly, under the given processing conditions, and with the special parent block copolymer architecture, the nanostructures of the block copolymer is maintained; there is no sign of macrophase‐separation as one would expect in the block copolymer blends comprising polystyrene with much higher molecular weight than the size of the corresponding block of the block copolymer. It should be noted that the molecular weight of GPPS used to prepare the blends has higher molecular weight (190,000 g/mol) . The PS chains should act as chains adhered feebly to the polystyrene domains of the block copolymer in the so called dry‐brush regime.…”
Section: Resultsmentioning
confidence: 89%
“…An overview of the morphology of some of the ST3/GPPS blends prepared by melt mixing followed by compression moulding is presented in Figure . The details on the morphology of the blends have been addressed in our earlier publications . Here, we summarize only the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on four arm SB star block copolymer/PS homopolymer (hPS) blends has revealed that the hardness increased with the increase in the PS‐layer thickness . The mechanical behaviour and morphology of blends of SB block copolymers and hPS have been repeatedly investigated in the last decade, mainly by Adhikari el al . The morphology of blends of an SB star block copolymer and PS, which ranges from microphase‐separated to macrophase‐separated structure depending on the molecular weight of the PS and the composition of the blends clearly affects the tensile mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…As known, polymers chemical composition and morphology influence the bulk properties (rheological behavior, mechanical properties). Block copolymers are of particular interest, because the combination of the single components can be balanced by using suitable molecular weights and amount of the coupled segments to obtain the characteristics required for the desired application 16–20. The mechanical properties are, in particular, an issue that has to be often faced when a material is implanted in the human body as temporary (e.g., bioerodible–bioeliminable scaffold) or permanent (e.g.…”
Section: Introductionmentioning
confidence: 99%